Splitting tensile and pullout behavior of synthetic wastes as fiber-reinforced concrete - Khalid, F.S.; Irwan, J.M.; Ibrahim, M.H. Wan; Othman, N.; Shahidan, S. (ScienceDirect, 2018)
Plastic bottles and waste wires are the most commonly discarded synthetic wastes that contribute to environmental pollution. Polyethylene terephthalate (PET) bottles act as one of the contributors to environmental pollution. One solution to environmental pollution includes recycling plastic bottle wastes as synthetic fibers and incorporating them into concrete. Therefore, pullout strengths of synthetic fibers in a concrete matrix should be investigated by conducting splitting tensile and pullout tests. Experiments of the present study used fibers from ring-shaped PET bottles with widths of 5 and 10 mm. Irregularly shaped PET bottles with 10–15 mm size, waste wires measuring 55 mm in length, and manufactured synthetic macro-fibers were also used in comparative analysis. Results indicate that an increase in fiber volume improves tensile strength of concrete. Incorporation of high-volume fiber with concrete results in a substantial amount of fibers bridging and crossing fractured sections, thereby activating failure resistance mechanisms. In comparison with irregularly shaped PET and waste wire fibers, ring-shaped fibers performed better as they are mainly designed to activate fiber yielding instead of fiber pullout. The load energy required to debond fibers and the concrete matrix was high when the surface contact area was large in comparison with that when a small surface contact area was considered. Fibers with small surface contact area easily slip under tensile stress. Thus, the surface contact area of fibers with concrete matrix allows good frictional resistance against pullout or tensile load